Hierarchical structures of AlOOH nanoflakes nested on Si nanopillars with anti-reflectance and superhydrophobicity - Yu, Eusun; Lee, Heon Ju; Ko, Tae-Jun; Kim, Seong Jin; Lee, Kwang-Ryeol; Oh, Kyu Hwan; Moon, Myoung-Woon (ROYAL SOC CHEMISTRY, 2013)
A novel method to fabricate ultra-low reflective Si surfaces with nanoscale hierarchical structures is developed by the combination of AlOOH or boehmite nanoflakes nested on plasma-etched Si nanopillars. Using CF4 plasma etching, Si surfaces are nanostructured with pillar-like structures by selective etching with self-masking by fluorocarbon residues. AlOOH nanoflakes are formed by Al thin film coating with various thicknesses and subsequent immersion in boiling water, which induces the formation of nanoscale flakes through the hydrolysis reaction. AlOOH nanoflakes are formed on Si nanopillared surfaces for hierarchical structures, which are coated with a low-surface-energy material, resulting in a higher water wetting angle of over 150 degrees and a very low contact angle hysteresis of less than 5 degrees, and implying a self-cleaning surface. Reflectance reduced to 5.18% on average on hierarchical nanostructures in comparison to 9.63% on the Si nanopillar surfaces only. We found that Si nanopillars reduced reflection for wavelengths ranging from 200 to 1200 nm while AlOOH nanoflakes reduced reflection for wavelengths longer than 600 nm.
Keywords: SILICON; WETTABILITY; COATINGS; SURFACES; OPTICS; FILMS